CLUSTERING KABUPATEN/KOTA PROVINSI SULAWESI TENGGARA BERDASARKAN INDIKATOR KESEJAHTERAAN RAKYAT - Andi Tenriawaru (Informatics Engineering Department of Halu Oleo University, 2018)
The problem of people's welfare is a problem that must be faced by developing countries such as Indonesia. Many indicators affect the level of people's welfare, such as population, education, levels and patterns of consumption, poverty, housing, and the environment. To make it easier in preparing plans or making decisions on issues of people's welfare, the government needs data and information regarding the level of people's welfare. Therefore, determining the level of people's welfare needs to be done.This study is intended to produce information on clustering districts/cities in Southeast Sulawesi Province based on indicators of people's welfare using the K-Means algorithm. The process of determining clusters consists of three processes i.e. Process of Collecting Datasets, Process of Clustering, and Process of Cluster Interpretation.The data used are data on people's welfare indicators from 12 districts/cities in Southeast Sulawesi for 2014. The data consists of seven variables, i.e. the Number of Health Facilities, Life Expectancy, the Projected Total Population, the Percentage of Non-Poor People, the Number of Administrative Regions, the Average Length of School, and Spending Per Capita. Based on the results of cluster analysis, it was found that the number of cluster members with low, medium, and high welfare indicators are 3, 6, and 3, respectively.Keywords—K-Means Algorithm, Cluster Analysis, Social WelfareDOI : 10.5281/zenodo.2528154